Experimental investigation of sustainable structural concrete incorporating completely recycled fine aggregate (CRFA): from material to structural levels - Yibo Yang; Yi Zhang; Baixi Chen; Wen Yang; Wenying Guo; Hengchang Wang (Low-Carbon Materials and Green Construction)
Abstract To mitigate the shortage of river sand and promote the reuse of construction waste, this study comprehensively evaluates the applicability of completely recycled fine aggregate (CRFA), produced by crushing concrete waste completely into fine aggregates, in structural concrete from the material to structural levels. Mechanical properties, durability, shrinkage, microstructure, and structural performance of recycled aggregate concrete (RAC) with CRFA as the sole fine aggregate were tested and compared to natural aggregate concrete (NAC) of the same strength grade. The results indicate that RAC exhibits comparable strength and elastic modulus to NAC at 28 days, although its long-term compressive strength is 12% lower. RAC demonstrates superior freeze–thaw resistance but reduced resistance to carbonation and chloride ion penetration due to a higher percentage of large pores, as observed via mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM). RAC also shows lower early-age autogenous shrinkage but higher long-term drying shrinkage than NAC. Structural testing under bending, axial, and eccentric compression reveals that RAC performs similarly to NAC and can be conservatively predicted by current design codes for NAC, with the ratios between experimental and predicted values exceeding 1.08. Furthermore, with 18.8% and 10.5% reductions in cost and carbon emissions, respectively, CRFA is an economical and sustainable alternative to river sand in structural applications.